2004
DOI: 10.1489/0020-7349(2004)72<278:votwoc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the WHO Operational Classification and Value of Other Clinical Signs in the Classification of Leprosy

Abstract: The objective of this study is to examine the validity of the WHO operational classification using skin smear results as the gold standard and explore the value of additional clinical signs independently and in combination with the WHO classification. Between 1985 and 2000, 5439 new untreated leprosy patients were registered at the Schieffelin Leprosy Research and Training Center, Karigiri. They were classified according to the Ridley Jopling classification as well as WHO operational classification based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
2
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
0
17
2
5
Order By: Relevance
“…A study by Norman et al (2004) reported that the sensitivity of WHO operational classification that classifies a patient with 6 or more lesions as multibacillary was 88.6% while the specificity was 86.7%. 25 Mehindiratta et al had only 74.6% cases correctly classified as multibacillary/ paucibacillary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Norman et al (2004) reported that the sensitivity of WHO operational classification that classifies a patient with 6 or more lesions as multibacillary was 88.6% while the specificity was 86.7%. 25 Mehindiratta et al had only 74.6% cases correctly classified as multibacillary/ paucibacillary.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Norman et al (2004) reported that the sensitivity of WHO operational classification that classifies a patient with 6 or more lesions as multibacillary was 88.6% while the specificity was 86.7%. 25 Mehindiratta et al had only 74.6% cases correctly classified as multibacillary/ paucibacillary. 26 Since 1966, the classification of leprosy by Ridley and Jopling into 5 subtypes (TT, BT, BB, BL, LL) based on clinical, histopathological and immunological features and bacteriological finding has been widely adopted by histopathologist and leprologist.…”
Section: Discussionmentioning
confidence: 99%
“…Se observó que alrededor de 50 % de las discrepancias encontradas en las lecturas de los se debe continuar utilizando para hacer una buena clasificación de los pacientes; además, se puede continuar utilizando en el seguimiento del tratamiento de la enfermedad, así como en la detección de recaídas, sin olvidar que se debe pensar en herramientas más sensibles para el seguimiento de los pacientes (21,22).…”
Section: Discussionunclassified
“…Sin embargo, Norman, et al, consideran que los laboratorios con técnicas bien estandarizadas y con un control de calidad funcional, hacen que los extendidos sean confiables (21).…”
Section: Discussionunclassified
“…However, it is extremely difficult to detect Mycobacterium leprae in an individual and various clinical and laboratorial criteria are used in the absence of an exam defined as a gold standard 2 . For treatment purposes, the World Health Organization (WHO) recommends an operational classification (OC), whereby patients are divided into paucibacillar (PB) when they present 5 cutaneous lesions or less, or multibacillar (MB) when they have more than 5 lesions 28 . However, when bacilloscopic examination is available, patients whose skin-smear exam tests positive are classified as MB regardless of the number of lesions.…”
mentioning
confidence: 99%